(untitled) (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2026)
The study aims to demonstrate the impact of social media use on the quality of accounting education after the COVID-19 pandemic. This study explores the impact of social media use on the exchange of ideas and opinions and accounting information, the impact of social media use on educational services, and the development of accounting research methods and concepts. The research community was selected from the teaching staff and students of accounting departments in Iraq. A random sample was selected from the community. Data for the current study was collected using a questionnaire designed for this purpose. (134) questionnaires were distributed, including (74) questionnaires to teaching staff and (60) questionnaires to students. The statistical program (SPSS) was used to describe the research sample, in addition to using the (T. Test) and the alpha reliability test to describe and analyze the study variables and test its hypotheses. The study concluded that there is a statistically significant impact of the use of social media on the quality of accounting education. The results showed that these media play an effective role in enhancing the presentation of opinions and ideas, exchanging accounting information, and providing educational services in more effective and flexible ways, in addition to their contribution to developing the methods and concepts of scientific accounting research. Among the most important recommendations made by the researchers, the study recommended the need to encourage the use of social media in accounting education, directing students towards using them as educational and research resources, and establishing specialized educational platforms managed by teaching staff.